Action nouns vs. nouns as bases for denominal verbs in Czech: A case study on directionality in derivation. (March 2021) - Ševčíková, Magda
Abstract : Suffixless action nouns are mostly analysed as deverbal derivatives (e.g., výběr 'choice' < vybírat 'to choose.ipfv '), but dictionaries ascribe the reverse direction to some noun–verb pairs ( útok 'attack' > útočit 'to attack.ipfv ') despite being both formally and semantically close to the former type. The question is addressed in the present study of whether any linguistic features can be identified in pairs of suffixless nouns and directly corresponding verbs that would speak in favour of one or the other direction. The analysis of 250 Czech suffixless nouns reveals a correlation between the number of directly related verbs derived by suffixes and the direction as recorded in the dictionaries: While deverbal nouns correspond mostly to a pair of verbs with different (aspect-changing) suffixes (cf. výběr 'choice' : vybrat / vybírat 'to choose.pfv /ipfv '), nouns that are bases for verbs tend to share the root with a single (imperfective) verb ( útok 'attack' : útočit 'to attack.ipfv '). This correlation is elaborated into two different paradigms, one being based on verbal roots and the other on nominal roots, which might be applicable in hypothesizing the direction also with nouns that are not covered by the dictionaries.